Effects of manipulating resistance training variables on post exercise blood pressure and heart rate variability - Alemi, Behzad (2019)
The purpose of this study was to compare blood pressure (BP) and heart rate variability (HRV) responses in physical active men after resistance training (RT) with different rest interval (RI) between sets (1, 2 and 3 minutes) and 3 different number of sets (3, 5 and 7 sets) with loads of 5 repetition maximum 5RM, 10RM, and 15RM. The HRV frequency-domain analysis provided high frequency (HF) and low frequency (LF) measurements which reflects sympathetic and parasympathetic activation. BP responses were measured in systolic (SBP) and diastolic (DBP). Due to large number of study variables we conducted two studies. Eighty-one men (21.6 ± 1.1yr; body mass: 74.1 ± 8.1kg; height: 175.3 ±7.1cm) who performed moderate to vigorous activities for a minimum of 30mins a day on at least five days a week participated in this study. After determination of 5RM loads for bent-over row, bench press, deadlift and squats, participants were divided into nine groups to perform different RT protocol in each group. Each group received different mixture of loads (5RM, 10RM or 15RM), Sets (3 Sets, 5 Sets or 7 Sets) and Rest Interval (1- min, 2-min or 3-min) for each exercise. All experimental sessions were performed in the following exercise order: squat, bench press, barbell bentover row followed by deadlift. Before and for two hours after each session, BP and HRV were measured. The results of the first study demonstrated low, moderate and high loads intensities (5RM, 10RM and 15RM) decreased SBP up until 120 min post-exercise. However, the DBP value remained low up until 105 min in 5RM and 15RM loads. Low frequency value was increased in 5RM, 10RM and 15RM up until 75, 90 and 60 min post exercise. The LF and HF values for each RIs between sets were not significantly differed among load intensities after RT session. In the second study results demonstrated low, moderate and high loads intensities (5RM, 10RM and 15RM) decreased SBP up until 75, 90 and 120 min post-exercise respectively. However, the DBP value remained low up until 90 min for 10RM and 15RM loads and low DBP value up until 45 min for 5RM load. Low frequency value was increased in 3, 5 and 7 sets up until 90, 105 and 120 min post-exercise respectively. High Frequency value was decreased in 3, 5 and 7 sets up until 90, 75 and 75 min post exercise respectively. The findings of this study showed a significant postexercise BP and HRV changes after RT in physical active men. The extent of the cardiac response was related to extended number of sets, rest intervals between sets and load intensities performed during training. Higher sets with a heavier load caused a greater response in BP and HRV. Thus, strength and protocol experts may prescribe higher number of exercise, longer rest intervals between sets and exercises with higher loads when the goal is to reduce BP after RT sessions as well as to minimise cardiac stress.